Negligence and Virtue: Errata Notices and their Evangelical Use. (14th June 2018) - Da Costa, Alexandra
Abstract: This essay is a comprehensive and detailed account of the use of errata notices in early English printing. It demonstrates that errata notices were almost unknown in books printed in English before the late 1520s and that they came into more frequent use because writers and printers saw their marketing or rhetorical potential and not because printers became more vigilant. In particular, it highlights the role evangelical writers had in this development, arguing that they were the first to adapt an apparatus more readily found in Latinate, scholarly works to their own vernacular productions, and they were doing so as early as 1526. In displaying an errata notice, evangelical editions drew attention to the value of their work and began a tradition in which an invitation to correct a vernacular text accorded it the esteem previously reserved for Latinate works.